Is it time to test biguanide metformin in the treatment of melanoma?. (26th June 2014) - Cerezo, Michael; Tomic, Tijana; Ballotti, Robert; Rocchi, Stéphane
Summary: Metformin is the most widely used antidiabetic drug that belongs to the biguanide class. It is very well tolerated and has the major clinical advantage of not inducing hypoglycemia. Metformin decreases hepatic glucose production via a mechanism requiring liver kinase B1, which controls the metabolic checkpoint, AMP‐activated protein kinase‐mammalian target of rapamycin and neoglucogenic genes. The effects of metformin on this pathway results in reduced protein synthesis and cell proliferation. These observations have given the impetus for many investigations on the role of metformin in the regulation of tumor cell proliferation, cell‐cycle regulation, apoptosis, and autophagy. Encouraging results from these studies have shown that metformin could potentially be used as an efficient anticancer drug in various neoplasms such as prostate, breast, lung, pancreas cancers, and melanoma. These findings are strengthened by retrospective epidemiological studies that have found a decrease in cancer risk in diabetic patients treated with metformin. In this review, we have focused our discussion on recent molecular mechanisms of metformin that have been described in various solid tumors in general and in melanoma in particular.